Vibrations influence on the operation of gears. (August 2019) - Ionica, V; Stanescu, M; Miritoiu, C; Geonea, I
Abstract: The purpose to optimize gears requires a very good understanding of their dynamic behaviour. Very important is the influence of vibrations on the operation of the gears. As a result of environmental constraints such as acoustics, gears are increasingly subject to stringent requirements in terms of load capacity, efficiency, noise and vibrations. The deformations of the gears involve deformations, in particular, located near the contacts that require great finesse. Gearboxes are equally sources of current vibrations as they are commonly used in industry. They are the subject of numerous studies to characterize their kinematic and dynamic behaviour. At present, research activities focus on the development of multidisciplinary experimental, theoretical and numerical skills that are put into play when designing structures, machine elements or, in general, mechanical systems. In this paper, we have proposed to find the dynamic response of the gearbox to the action of external disturbing factors. To this end, we have called for the use of integral transformations which, algebraizing the problem, greatly simplifies calculations.